2012
DOI: 10.7314/apjcp.2012.13.1.361
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β-tubulin III and Survivin in Advance Stage Breast Cancer Correlates with Chemotheraputic Effects of Docetaxel

Abstract: Aims: To investigate the relationship between the expression of β-tubulinⅢ and survivin in advanced breast cancers and chemotherapeutic effects of docetaxel. Methods: Clinical pathological data of 74 patients with advanced breast cancer were retrospectively analyzed after docetaxel chemotherapy. Expression of β-tubulinⅢ and survivin was assessed by immunohistochemistry and analyzed with reference to therapeutical and adverse effects of docetaxel. Results: The positive expression rate of β-tubulinⅢ was 38.1% (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
1
15
2
Order By: Relevance
“…The spectrum of cytoplasmic survivin expression 64.9 22.6 The density of cytoplasmic survivin expression 1.6 0.6 The index ofcytoplasmic survivin expression 4 (1-12) The spectrum of nuclear survivin expression 6.1 8.2 The density of nuclear survivin expression 2 0.5 The index of nuclear survivin expression 2 (0-6) the member of apoptosis protein inhibitor (IAP) family inhibiting apoptosis in a different way since its members certain bc l-2 family (Yuan et al, 2012). Apoptosis is the important event kept under control by various activator and inhibitor factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum of cytoplasmic survivin expression 64.9 22.6 The density of cytoplasmic survivin expression 1.6 0.6 The index ofcytoplasmic survivin expression 4 (1-12) The spectrum of nuclear survivin expression 6.1 8.2 The density of nuclear survivin expression 2 0.5 The index of nuclear survivin expression 2 (0-6) the member of apoptosis protein inhibitor (IAP) family inhibiting apoptosis in a different way since its members certain bc l-2 family (Yuan et al, 2012). Apoptosis is the important event kept under control by various activator and inhibitor factors.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin, a member of apoptosisinhibitor gene family, is expressed in G2/M in most normal tissues with terminal differentiation, the newly researches have demonstrated that survivin is extremely expressed in various cancer types (Altieri et al, 1999;Karimi et al, 2013). In several studies, the extreme expression of survivin is related to bad prognosis in urinary bladder cancer (Srivastava et al, 2013), cervix uteri cancer (Cao et al, 2014), colorectal cancer (Yuan et al, 2012) and breast cancer (Damitri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the association of βIII-tubulin expression with response to taxane treatment. Yuan et al18 investigated βIII-tubulin expression in advanced breast cancer with docetaxel therapy. They reported that there were significant differences between the effective rate (CR+PR) of patients with positive expression of βIII-tubulin (37.50%) and that of patients negative for expression (61.54%) (p<.01).…”
Section: Discussionmentioning
confidence: 99%
“…Survivin, a new member of the inhibitor of apoptosis protein (IAP) family, both inhibits apoptosis and regulates the cell cycle (Yuan et al, 2012). It is overexpressed in breast tumor tissues, but hardly expressed in most normal tissues (Montazeri et al, 2012;Yakirevich et al, 2012).…”
Section: Discussionmentioning
confidence: 99%